Control of large institutional scabies outbreaks - Stoevesandt, Johanna; Leverkus, Martin (Journal der Deutschen Dermatologischen Gesellschaft, 2012)
Background: Scabies outbreaks in community facilities may reach large dimensions and take a protracted course. Highly contagious crusted scabies is a major cause of nosocomial outbreaks. Patients and methods: On the occasion of an extensive scabies outbreak in a north Bavarian sheltered workshop and its associated residential homes with over 500 exposed individuals, a multifaceted control strategy was developed and pursued. Knowledge from a comprehensive review of the literature was utilized. Results: Our successful scabies elimination concept includes: 1) Careful organization (formation of an outbreak management team, registration and information of all exposed individuals, prospective time management, financial calculation); 2) simultaneous clinical examination of all individuals at risk; 3) synchronous topical treatment of all exposed individuals with permethrin 5 % cream on day 0, repeated treatment of proven and doubtful cases on days 1 and 14; systemic treatment of selected cases with oral ivermectin; 4) decontamination and quarantine measures; 5) follow-up investigations and repeated treatment if indicated. Conclusions: Management of large institutional scabies outbreaks requires a high degree of motivation, communication skills and perseverance.